Synthesis of heterocycles compounds from condensation of limonene with aldehydes using heteropolyacids supported on metal oxides (2022)
In this contribution, heterogeneous materials based on heteropolyacids (HPA, H3PW12040 hydrate) supported over several metal oxides (TiO2, SiO2, SBA-15, Al2O3) were prepared using wetness impregnation, characterized by XRD, FTIR, SEM, acidity by TPD, nitrogen physisorption, RAMAN spectroscopy, 31P NMR and then evaluated in the catalytic condensation of limonene with benzaldehyde. After incorporation of HPA over each support, no structural changes were observed as it was suggest by FTIR, RAMAN and XRD. Acidity analysis by TPD-NH3 showed that increasing the HPA amount increases the acidity of the catalyst until it is constant (20–30%). HPA over alumina, silica and SBA-15 also showed high values of acidity but less than typical HPA/P25 catalyst (HPA over commercial Degussa P25). This last was one of the most selective materials (surface area of 39 m2 /g and acidity of 187 µmol NH3. gcat − 1) for the synthesis of 3-oxabyciclo[3.3.1]nonane (up to 80%) with a low selectivity to the limonene isomers by-products. The use of water as a solvent decreased considerably the catalytic activity. The same observation was found when the volume of the solvent increased to 30 mL. Besides, catalytic condensation can be performed at free solvent conditions and at room temperature; however, when decrease temperature, a higher number of isomers was observed rather than the desired product. In addition, catalytic condensation was also evaluated in biomass of essential oils and mixtures with sesquiterpenes showing good to excellent results. Typical LHHW mechanism was evident after kinetic analysis. HPA/P25 was shown to be a robust material since can be reused up to two times with a possible decrease in its catalytic activity.